Religious Resilience of Tulungagung Community Through Busyro Salawat at Majelis Assyifa - Setiawan, Aria Nur; Ubaidillah, Ubaidillah; Marpuah, Siti (IAIN Palangka Raya, 2024)
The increasing social unrest, value uncertainty, and spirituality challenges in today's modern era, encourage the need to understand the practice of sholawat as a living hadith heritage that can provide spiritual direction in the midst of the challenges of the times. The aim of the research was to analyze the religious resilience of Tulungagung community through busyro salawat at Majelis Assyifa. The particular research used a qualitative approach, which produces descriptive data through verbal and written notes, and involves observing the behavior of people who are the object of research. Then, the data was analyzed using Max Weber's social action approach theory. The results showed that the practice of salawat busyro in Majelis Assyifa Tulungagung in understanding through the lens of living hadith, not only provides spiritual wisdom, but also provides a relevant and adaptive value framework that can significantly bring a sense of calmness, wisdom in overcoming complex social, and spiritual issues of the times.